Evolutionary and Biologically Inspired Music, Sound, Art and Design Second International Conference, EvoMUSART 2013, Vienna, Austria, April 3-5, 2013. Proceedings - Machado, Penousal; McDermott, James; Carballal, Adrian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the Second International Conference on Biologically Inspired Music, Sound, Art and Design, EvoMUSART 2013, held in Vienna, Austria, in March 2013, colocated with the Evo* 2013 events EuroGP, EvoCOP, EvoBIO, and EvoApplications. The 11 revised full papers and 5 poster papers presented were carefully reviewed and selected from 36 submissions. They cover a wide range of topics and application areas, including: generative approaches to music, graphics, game content, and narrative; robot gait creation; music information retrieval; computational aesthetics; the mechanics of interactive evolutionary computation; and the art theory of evolutionary computation.
Keywords: Computer science; Computer software; Artificial intelligence; Information systems; Computer Science; User Interfaces and Human Computer Interaction; Algorithm Analysis and Problem Complexity; Artificial Intelligence (incl. Robotics).; Computer Appl. in Arts and Humanities